2017
DOI: 10.1002/jcp.25968
|View full text |Cite
|
Sign up to set email alerts
|

Isorhapontigenin induced cell growth inhibition and apoptosis by targeting EGFR‐related pathways in prostate cancer

Abstract: Isorhapontigenin (ISO), a naturally phytopolyphenol compound existing in Chinese herb, apples, and various vegetables, has attracted extensive interest in recent years for its diverse pharmacological characteristics. Increasing evidences reveal that ISO can inhibit cancer cell growth by induced apoptosis, however, the molecular mechanisms is not fully understood. In this study, we found for the first time that ISO apparently induced cell growth inhibition and apoptosis by targeting EGFR and its downstream sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
3
20
0
1
Order By: Relevance
“…ISO at a concentration of 100 µM decreased prostate cancer LNCaP and CWR22Rv1 cells viability to 25% and 45%, respectively. On the other hand, the weak effect was exerted on BPH-1 and WPHY-1 cells, where cell viability was~80% after ISO treatment at the same treatment conditions [64]. This study showed that ISO might bind to epidermal growth factor receptor (EGFR) and inhibit its autophosphorylation and downstream signallings, such as PI3K/Akt and extracellular signal-regulated kinase 1/2 (ERK1/2) pathway.…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 94%
See 1 more Smart Citation
“…ISO at a concentration of 100 µM decreased prostate cancer LNCaP and CWR22Rv1 cells viability to 25% and 45%, respectively. On the other hand, the weak effect was exerted on BPH-1 and WPHY-1 cells, where cell viability was~80% after ISO treatment at the same treatment conditions [64]. This study showed that ISO might bind to epidermal growth factor receptor (EGFR) and inhibit its autophosphorylation and downstream signallings, such as PI3K/Akt and extracellular signal-regulated kinase 1/2 (ERK1/2) pathway.…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 94%
“…Another study showed anticancer activity of ISO against prostate cancer LNCaP and CWR22Rv1 cell lines. It should be emphasized that ISO did not affect cell viability against benign hyperplasia epithelial cells (BPH-1) and healthy prostate cells (WPMY-1) [64]. It was shown using MTT assay that ISO inhibited the viability of LNCaP and CWR22Rv1 in a dose-dependent manner.…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 97%
“…Isorhapontigenin (ISO) is widely distributed in Chinese herbs, fruits, and vegetables [ 54 , 55 , 56 ]. Isorhapontigenin (ISO, 20–100 μM) induced cell growth inhibition and apoptosis of LNCaP and 22Rv1 by targeting EGFR and its downstream signal pathways and showed no obvious effects on normal prostate cells [ 57 ]. Moreover, the treatment with ISO decreased the protein level of AR by promoting the ubiquitination and degradation of AR proteins in proteasome and inhibiting the expression of AR gene [ 57 ].…”
Section: Compounds Isolated From Chinese Medicines Inhibit Prostatmentioning
confidence: 99%
“…Isorhapontigenin (ISO, 20–100 μM) induced cell growth inhibition and apoptosis of LNCaP and 22Rv1 by targeting EGFR and its downstream signal pathways and showed no obvious effects on normal prostate cells [ 57 ]. Moreover, the treatment with ISO decreased the protein level of AR by promoting the ubiquitination and degradation of AR proteins in proteasome and inhibiting the expression of AR gene [ 57 ]. In vivo, 50 mg/kg of ISO inhibited the growth of subcutaneously xenotransplanted tumors in nude mice by inducing PCa cell growth inhibition and apoptosis [ 57 ].…”
Section: Compounds Isolated From Chinese Medicines Inhibit Prostatmentioning
confidence: 99%
See 1 more Smart Citation